Biodisponibilidade de cobre em lixiviado de rejeitos da mina de Pedra Verde, em Viçosa do Ceará, e seu potencial de contaminação para a água e para o solo - Martins, Eve Pimentel (2018)
The potential emission of Cu2+ ions from ‘Pedra Verde‘ abandoned copper mine to the environment, its concentration and biogeochemistry will be studied on the water and soil. Experiments were carried out in pots containing samples from a dandy soils and a clayey soil without contamination collected upstream of the Pedra Verde Mine to avoid contamination by copper. These soils had pH and Cu content analyzed to serve as reference. The wastes were added above the soils without contamination and exposed to the site. The Cu contents were determined in the solution leached via atomic absorption and in the soil by means of sequential extraction to evaluate the bioavailability of the metal. To determine the water quality, basic parameters such as pH and electrical conductivity were evaluated. After three months of experiments there was an average increase of the total content of copper in the sandy soil equal to 21%, whereas for the clayey soil there was an average increase of the total Cu content equal to 39%. For the leachate of the sandy soil, the average of the total content of Cu found in the pots was 0.60 mg/L of Cu, while the average of the total content of Cu was 0.34 mg/L of Cu. After three months of experiment the sequential extraction, performed in both soils, shows a increase in Cu content associated with more mobile fractions, increasing its bioavailability to the environment. The results corroborate the initial hypothesis that the deposition of open-pit copper sulfate and carbonated ore tailings exposed to rainfall are potential sources of contamination to soil and water even after decades of exhibition. It was evident that the soil characteristics of these wastes clearly influence the mobility of the metal. The study has as a benefit the knowledge of the cooper contents emitted by these wastes to the environment, being important for the design of control measures and mitigation of impacts.